Three years’ interventional neurology experience in Turkey with the Thrombite thrombectomy device in large vessel occlusion in the anterior circulation: safety, efficacy, and clinical outcome - Akpınar, Çetin Kürşad; Gurkas, Erdem; Ozdemir, Atilla Ozcan; Doğan, Hasan; Önalan, Ayşenur; Yıldırım, Serhan; Memiş, Zülfikar; Aytaç, Emrah; Acar, Bilgehan Atılgan; Öğün, Muhammed Nur; Aykaç, Özlem; Uysal Kocabaş, Zehra; et al. (Frontiers in Neurology, 2024)
Introduction: While the Thrombite device differs from the Solitare stent with its Helical openside structure feature, it shows great similarity with its other features. In this study, the safety and efficacy of the Thrombite device were evaluated. Material and Method: Patients who were enrolled in Turkish Interventional Neurology database and underwent mechanical thrombectomy using the Thrombite device as the first choice between January 2020 and January 2023 were included in the study and analyzed retrospectively. The type of study is descriptive research. Result: Five hundred five patients were treated with the Thrombite TM thrombectomy device. The mean patient age was 68.6+11.7 years, the median baseline National Institutes of Health Stroke Scale (NIHSS) was 13, and the median initial Alberta Stroke Program Early Computed Tomography (ASPECT) score was 8. The median time from groin puncture to successful recanalization was 34 min (interquartile range (IQR): 15-45). First-pass recanalization rates were 48.2% (modified treatment in cerebral infarction (mTICI) 2b/3) and 33.9% (mTICI 2c/3).Final successful recanalization rate was 87.7% (thrombolysis in cerebral infarction 2b/3).Favorable functional outcome (modified Rankin Scale 0-2) was 51.8% in the "first-pass" subgroup and 41.6% in the total patient population. The rate of embolization into new territory/different territory were 2.1/0.1%. 23 patients (4.5%) had symptomatic hemorrhage.In our experience, the Thrombite device demonstrated high overall succesfull recanalization rates and good safety profile.